Особливості реалізації процесів автоматизації та реагування на кіберзагрози у хмарних середовищах - Фісенко, Д. М.; Білодід, В. Г. (ХНУРЕ, 2025)
This work is devoted to determining the features of implementing security orchestration, automation and response approach. The main features and benefits of the approach were considered. The combination of SOAR and Machine Learning (ML) is critical to modern cybersecurity, enabling organizations to respond to threats faster, manage incidents more effectively, and improve the accuracy of anomaly detection.
Keywords: кіберзагроа; хмарне середовище